Identification of the Ferroptosis-Related Long Non-Coding RNAs Signature to Improve the Prognosis Prediction in Papillary Renal Cell Carcinoma - Tang, Xinfang; Jiang, Feng; Wang, Xiaoyu; Xia, Ying; Mao, Yan; Chen, Yan (Frontiers in Surgery, 2022)
Papillary renal cell carcinoma (pRCC) is one of the epithelial renal cell carcinoma (RCC) histological subtypes. Ferroptosis is a new iron-dependent form of cell death that has been seen in a variety of clinical situations. Using differentially expressed ferroptosis-related lncRNAs from pRCC patients in TCGA, we built a prognostic lncRNA-based signature. We discovered seven different lncRNAs that were strongly linked to the prognosis of pRCC patients. High risk scores were linked to a poor prognosis for pRCC, which was confirmed by the findings of Kaplan-Meier studies. In addition, the constructed lncRNA signature has a 1-year AUC of 0.908, suggesting that it has a high predictive value in pRCC. In the high-risk group, GSEA analysis identified immunological and tumor-related pathways. Furthermore, ssGSEA revealed significant differences in T cell functions checkpoint, APC co-stimulation, inflammation promoting, and para inflammation between the two groups with different risk scores. In addition, immune checkpoints like PDCD1LG2 (PD-L2), LAG3, and IDO1 were expressed differently in the two risk groups. In summary, a novel signature based on ferroptosis-related lncRNAs could be applied in predicting the prognosis of patients with pRCC.